Expanding the mutational and clinical spectrum of Chinese intellectual disability patients with two novel CTCF variants - Tan, Bo; Liu, Sihan; Feng, Xiaoshu; Pan, Xin; Qian, Guanhua; Liu, Li; Zhang, Xu; Yao, Hong; Dong, Xiaojing (Frontiers in Pediatrics, 2023)
CCCTC-Binding Factor (CTCF) is a protein-coding gene involved in transcriptional regulation, insulator activity, and regulation of chromatin structure, and is closely associated with intellectual developmental disorders. In this study, we report two unrelated Chinese patients with intellectual disability (ID). According to variant interpretation results from exome sequencing data and RNA-seq data, we present two novel heterozygous CTCF variants, NM_006565.3:c.1519_2184del (p. Glu507_Arg727delins47) and NM_006565.3:c.1838_1852del (p.Glu613_Pro617del), found in two distinct unrelated patients, respectively. Moreover, RNA-seq data of patient 1 indicated the absence of the mutant transcript, while in patient 2, the RNA-seq data revealed a CTCF mRNA transcript with a deletion of 15 nucleotides. Notably, the RNA sequencing data revealed 507 differentially expressed genes shared between these two patients. Specifically, among them, 194 were down-regulated, and 313 were up-regulated, primarily involved in gene regulation and cellular response. Our study expands the genetic and clinical spectrum of CTCF and advances our understanding of the pathogenesis of CTCF in vivo.